Identifikasi Permasalahan dan Kerangka Pengembangan Kluster UMKM Sandang di Bukittinggi Sumatera Barat - Riani, Novya Zulva (Fakultas Ilmu Sosial Universitas Negeri Padang, 2011)
ABSTRACT Identification of the problem of UMKM is divided into two groups: internal problems which include issues of organizational structure, organizational strategy, and competition and external group problems that include broad market issues, problems of input and output factor conditions supporting institutional and industrial problems. This research concluded that the internal problems of UMKM in Bukittinggi is the lower level of owner education and the UMKM management is still indicated traditional, while the external problems are the limitation of market share and access to financial institutions that are still difficult. Kata Kunci: Klaster, permasalahan internal dan eksternal, UMKM, industri, sandang